High-latitude cooling associated with landscape changes from North American boreal forest fires - Rogers, B. (author); Randerson, J. (author); Bonan, Gordon (author) (Biogeosciences, 2013)
Fires in the boreal forests of North America are generally stand-replacing, killing the majority of trees and initiating succession that may last over a century. Functional variation during succession can affect local surface energy budgets and, potentially, regional climate. Burn area across Alaska and Canada has increased in the last few decades and is projected to be substantially higher by the end of the 21st century because of a warmer climate with longer growing seasons. Here we simulated changes in forest composition due to altered burn area using a stochastic model of fire occurrence, historical fire data from national inventories, and succession trajectories derived from remote sensing. When coupled to an Earth system model, younger vegetation from increased burning cooled the high-latitude atmosphere, primarily in the winter and spring, with noticeable feedbacks from the ocean and sea ice. Results from multiple scenarios suggest that a doubling of burn area would cool the surface by 0.23 ± 0.09 °C across boreal North America during winter and spring months (December through May). This could provide a negative feedback to winter warming on the order of 3-5% for a doubling, and 14-23% for a quadrupling, of burn area. Maximum cooling occurs in the areas of greatest burning, and between February and April when albedo changes are largest and solar insolation is moderate. Further work is needed to integrate all the climate drivers from boreal forest fires, including aerosols and greenhouse gasses.